Natural degradable protein and roughage type for implanted finishing steers fed dry-rolled corn diets - Milton, C.T.; Brandt, Robert T., Jr.; Kuhl, Gerry L.; Titgemeyer, Evan C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred eighty-four crossbred, yearling steers (810 lb) were used to evaluate soybean meal (SBM), sunflower meal (SFM), and combinations of the two as protein supplements and supplemental protein effects in diets containing silage or alfalfa as dietary roughage. All diets contained 1.0% urea (dry matter basis). An additional 2 percentage units of crude protein were either not provided or provided as SBM, SFM, or a 50:50 combination (protein basis) of SBM and SFM. Steers were implanted with Revalor-Sfi and fed experimental diets for 126 days. No interactions between protein supplementation and roughage source were observed. Daily feed intake and feed efficiency were unaffected by additional supplemental protein compared to urea alone. Averaged across both roughage sources, provision of supplemental SBM tended to increase daily gain. Dressing percentage decreased when supplemental SBM was provided and increased when alfalfa was fed as the roughage source. Based on carcass-adjusted performance, feeding alfalfa as the dietary roughage source improved daily gain by 3.9% and feed efficiency by 4.8% compared to sorghum silage. Carcass finish, marbling score, and carcasses grading Choice were unaffected by treatment. Carcass-adjusted growth rate and conversion efficiency were enhanced when alfalfa was fed independent of dietary crude protein concentration.
Keywords: Beef; Sunflower meal; Soybean meal; Urea; Finishing steers